Uncoupled Dynamics Do Not Lead to Nash Equilibrium - Hart, Sergiu; Mas-Colell, Andreu (American Economic Review, 2003)
The following sections are included:The ModelAn Example with a Continuum of StrategiesAn Example with Finitely Many StrategiesDiscussionAppendixReferences